2008
DOI: 10.1093/intimm/dxn044
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative and qualitative deficiencies of regulatory T cells in patients with systemic lupus erythematosus (SLE)

Abstract: The objective of the study was that the regulatory T cells (Treg) that specialize in the suppression of immune responses might be critically involved in the pathogenesis of autoimmune disease. As for systemic lupus erythematosus (SLE), however, published data concerning Treg phenotype and function are partly conflicting. We therefore performed quantitative and qualitative analyses of naturally occurring CD4(+)CD25(+) Treg from SLE patients as compared with healthy controls (HC) in order to further elucidate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
146
2
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(161 citation statements)
references
References 34 publications
8
146
2
5
Order By: Relevance
“…2,7 The various Treg cells have key roles in maintaining self-tolerance and modulating the allergic and autoimmune responses, while controlling autoreactive T cells. [8][9][10][11] Several studies have reported a deficiency in the number of Treg and/or function in autoimmune disease patients, 12,13 namely in systemic lupus erythematous, 14 rheumatoid arthritis, 15 multiple sclerosis, 16 autoimmune polyglandular syndrome II, 17 myasthenia gravis 18 and type I diabetes. 19 However, results concerning the number of circulating Treg cells and their suppressive function have been contradictory.…”
Section: Introductionmentioning
confidence: 99%
“…2,7 The various Treg cells have key roles in maintaining self-tolerance and modulating the allergic and autoimmune responses, while controlling autoreactive T cells. [8][9][10][11] Several studies have reported a deficiency in the number of Treg and/or function in autoimmune disease patients, 12,13 namely in systemic lupus erythematous, 14 rheumatoid arthritis, 15 multiple sclerosis, 16 autoimmune polyglandular syndrome II, 17 myasthenia gravis 18 and type I diabetes. 19 However, results concerning the number of circulating Treg cells and their suppressive function have been contradictory.…”
Section: Introductionmentioning
confidence: 99%
“…13 Recent studies found that missing or dysfunction of Treg cells can lead to a variety of autoimmune diseases such as SLE and RA. 14,15 The balance of Th17/Treg controls immune response and has been reported to be a key factor in regulating Th cell function relating to the Th1/Th2 shift in autoimmune diseases and graft vs host disease. 16 Emerging evidence suggests that Th17/Treg imbalances contributes to the development of autoimmune diseases, such as SLE 17 and primary nephrotic syndrome.…”
mentioning
confidence: 99%
“…In addition to upregulated effector T cell responses, SLE patients have reduced numbers and impaired function of CD4+ regulatory T cells (Treg) [11]. An imbalance between Th17 cells and Treg, with higher ratio of Th17 to Treg cells compared to healthy controls has also been reported in SLE [12•].…”
Section: T Cell Subsets In Slementioning
confidence: 99%